(untitled) (Altre Modernità, 2016)
This text is based on the idea of how mass-media produce an invisible but powerful general pedagogy. In the case of the cinema, in a context of cultural globalization, image produces and reproduces visions of the social world. It is important and necessary to rethink critically the social space through its representation in a few number of famous and representative contemporary films. Thus, this article attempts to understand the collective imagination, its limits and its forms of cultural and political influence in today’s society.